Environmental Risk in the Credit Research and Rating Process: The Case of UK Electricity Generators - Freund, Jessica (2012)
The impact of environmental factors on financial bottom lines is a concept that has been widely debated for decades. Research attempting to address the debate and provide answers for practitioners has resulted in mixed results. However our economies fall victim to the detrimental effects of climate change, the impacts of environmental hazards are becoming less deniable. The management of some the world’s largest corporations acknowledge this risk and recognize opportunity to mitigate their exposure to a changing climate often while increasing operational efficiency and creating a more sustainable future for the corporation. In the investment realm, an acceptance of the potential risk and opportunity of environmental, social, and governance (ESG) factors has grown with many investors now actively seeking out information pertaining to ESG allowing them to make better informed decisions and maximize the returns on their portfolio. However, the rating systems most depended on by investors have not necessarily moved at the same speed with environmental factors often still being overlooked in the research process. This study aims to address this concern by considering one of the most influential tools in the bond investing market, a corporate credit rating, and evaluate the integration of environmental risk into the credit research and rating process.